Effect of alkyl chain length on the thermophysical properties of pyridinium carboxylates - Rashid, T. (Chemical Industry Press, 2017)
In the present study, new series of pyridinium carboxylate protic ionic liquids (PILs) were synthesized by pairing pyridinium cation with carboxylate anion from C1–C3 forming pyridinium formate (C5H6N+HCOO−), pyridinium acetate (C5H6N+CH3COO−) and pyridinium propionate (C5H6N+CH3CH2COO−) respectively. The physical properties namely, density, viscosity, surface tension (298.15–343.15) K, and refractive index (293.15–323.15) K were measured. Thermal properties namely, glass transition temperature, molar heat capacity, and thermal decomposition temperatures were also determined. The thermal expansivity was calculated using the experimental density data. The effect of increasing the alkyl chain length on the thermophysical properties of the pyridinium carboxylate PILs has been evaluated. As expected the physical properties i.e. density, viscosity, surface tension and refractive index of the investigated pyridinium carboxylates decreased with increasing temperature. In general pyridinium carboxylate PILs possessed low viscosity, high thermal stability and excellent hydrogen bonding capability, and these properties lead them to outperform conventional solvents employed for lignin dissolution. © 2016 Elsevier B.V.